Enhancing the role of inspection agencies in prevention and anti-corruption from reality in Hai Duong province : Luận văn ThS. Quản lý công (Chương trình đào tạo thí điểm) - Nguyễn Quốc Khánh (H.: ĐHKT, 2018)
67 p.